The expanded program on immunization service delivery in the Dschang health district, west region of Cameroon: a cross sectional survey - Walter Ebile Akoh; Jérôme Ateudjieu; Julienne Stephanie Nouetchognou; Martin Ndinakie Yakum; Fabrice Djouma Nembot; Sonia Nafack Sonkeng; Micheal Saah Fopa; Pierre Watcho (BMC, 2016)
Abstract Background Vaccination is the most effective intervention strategy, and the provision of vaccination at fixed posts and outreach posts is a backbone of a sustainable vaccination system in developing countries. Access to immunization services is still limited in Cameroon. Several health districts in the west region have recorded new epidemic outbreaks, including the occurrence of a wild polio virus epidemic outbreak in 2013. The aim of this study was to assess immunization service delivery in one of the largest health districts in the west region of Cameroon; the Dschang Health district. Methods It was a cross sectional study conducted in 2013, in 42 health facilities covering 18 health areas in the Dschang Health District. Data were collected with questionnaires administered to health personnel face to face and an observation grid was used to assess resources and tools. Data were entered and analyzed in Epi Info. Results A total of 42 health facilities were assessed and 77 health personnel were interviewed. Overall, 29 (69.0 %) health facilities organized one vaccination session monthly, 2 (4.8 %) organized an outreach within the last 3 months prior to the study, 15 (35.7 %) did not have a vaccination micro plan, 24 (32.9 %) health personnel had not been supervised for at least the last 6 months prior to the study, 7 (16.7 %) health facilities did not have a functional refrigerator, 1 (2.4 %) did not have a vaccine carrier, 23 (54.8 %) did not have a means of transport (vehicle or motorcycle) and 12 (28.6 %) did not have an EPI guideline. The knowledge of health personnel on vaccine and cold chain management, and on diseases of the EPI under epidemiological surveillance was found to be limited. Conclusion The frequency and strategic provision of immunization services in the Dschang Health district is inadequate. Resource availability for an adequate provision of immunization services is insufficient. The knowledge of health personnel on vaccine management, cold chain management and on diseases under surveillance by the EPI is limited.